Natureza e alcance do conceito de subimperialismo no capitalismo contemporâneo: um estudo de caso sobre a economia brasileira - Brandão, Danilo Duarte (2019)
The theory of imperialism is a reference for the study of the functioning of contemporary capitalism and is thus used as a starting point for understanding the role of dependent economies in the international division of labor. The Marxist Theory of Dependency is a fundamental theoretical framework of critical thinking for the study of the development of Latin American economies. It also contributes important concepts such as: the overexploitation of the labor force and sub-imperialism; coined by Ruy Mauro Marini. After this, the work carries out a study of the Brazilian economy through the concept of sub-imperialism. The industrialization of the Brazilian economy raises the average organic composition of capital in the mid-1960s; deepens its integration with US imperialism and maintains a relative autonomy with expansionist policy that assists in the realization of capital via foreign trade and capital export. However, the state’s fiscal and financial crisis in the 1970s and 1980s imposed limits on development policies. The 1990s mark the beginning of neoliberal policies, in line with the Washington Consensus, resulting in market opening, financial liberalization, and lack of industrial policy. Thus, it is sought to answer if the concept of sub-imperialism still has an explanatory capacity for the Brazilian economy in the 21st century, given the loss of the dynamism of national industry and capitalist competition. To this end, the composition of the export agenda of Brazil with its main trading partners, the positioning of the country in the face of US imperialism’s investees in South America, the mergers and acquisitions of the Brazilian transnationals in the countries of the region and the Brazilian direct investment. The result found, reveals that the term sub-imperialism is still valid for the Brazilian economy, but the US and Chinese interests in South America combined with the internal weaknesses to resume industrial policies limit the conditions for sub-imperialism.